Representation of multicultural value in animation film Upin-Ipin seasion 6 "Ghost Month" - Sudono, Sudono; Kuswatoro, RB Hendri (Informasi, 2023)
In the era of advances in information technology, early childhood education can use various media, including film, which is considered a very effective means of conveying messages or ideologies with audio-visual power. The animated film Upin-Ipin, as one of the contestants in the arena of animated film ideology, has an important role in instilling moral values in children. Through the moral message conveyed through the film, the personality formation of young children can be aligned with the moral message conveyed. This study, which applies a qualitative research approach with library methods, uses primary and secondary data as sources of information. Observation and documentation techniques were used to collect data, while data analysis adopted Roland Barthes' semiotic analysis model. The results of the study show that the animated film Upin and Ipin presents multicultural values as part of their Islamic identity, which is reflected in their friendly relationships with characters such as Jarjit (of Indian descent) and Mei-mei (of Chinese descent). Despite coming from different religious and ethnic backgrounds, Upin-Ipin and their friends can interact harmoniously, creating an inclusive playing environment.